solve this : ( x+2 ) (x+3) + (x-3) (x-2) - 2x ( x+1 ) = 0
Answers
Answered by
1
x²+2x+3x+6+x²-2x-3x+6-2x²-2x = 0
12-2x = 0
12 = 2x
x = 6
Hope it helps you. If yes, then please mark it brainliest.
Answered by
15
ツ ¸.•°*”˜ ˜”*°•.¸
║╦╔╗║║╔╗║
╠╣╠╝║║║║║
╩║╚╝╚╚╚╝O
(x+2) (x+3) + (x-3) (x-2) -2x(x+1)=0
=> x²+3x+2x+6+x²-2x-3x+6-2x²-2x=0
=> 2x²-2x²+6x-6x-2x+12=0
=> -2x+12=0
=> -2x=0-12
=> -2x=-12
=> x=12/2
=> x=6
hope it helps uh!
(\_(\
(。- .•)
o_(“)(“)
║╦╔╗║║╔╗║
╠╣╠╝║║║║║
╩║╚╝╚╚╚╝O
(x+2) (x+3) + (x-3) (x-2) -2x(x+1)=0
=> x²+3x+2x+6+x²-2x-3x+6-2x²-2x=0
=> 2x²-2x²+6x-6x-2x+12=0
=> -2x+12=0
=> -2x=0-12
=> -2x=-12
=> x=12/2
=> x=6
hope it helps uh!
(\_(\
(。- .•)
o_(“)(“)
Similar questions